The Influence Of Innate Psychological Needs On Intention To Stay Among Academics Employed At Malaysian Research Universities - Ong, Yean Sze (2022)
This study examined the relevance of innate psychological needs among Malaysian academics in the context of Malaysian research universities. It encompasses the innate psychological needs for autonomy, competence, and relatedness that can influence the intention to stay. A model was developed based on the self-determination theory to identify the predictors of innate psychological needs to examine how influential factors in three innate psychological needs can enhance the intention to stay through employee engagement. This study investigated how employee engagement plays a mediating role between innate psychological needs and the intention to stay. This study also investigated the relationship between employee engagement and the intention to stay. In addition, this study also examined how perceived organizational support moderates the relationship between innate psychological needs and employee engagement. Data was collected from 329 Malaysian academics from five Malaysian research universities via an online survey questionnaire developed from related literature. The collected data was then analyzed using Smart PLS. Findings indicate that innate psychological needs for autonomy (job autonomy), competence (social status), and relatedness (psychological ownership) have a significant positive impact on employee engagement.